Perancangan Permainan Gelembung Huruf (Tokoh Wayang) Berbasis Sistem Operasi iOS Menggunakan Gamesalad - Adhitama Ksatriya Nugraha; Kodrat Iman Satoto; Rinta Kridalukmana (Jurnal Teknologi dan Sistem Komputer, 2014)
Currently, the globalization and modernization of the country make us forget the traditional culture. Not surprisingly, more people are not familiar with puppet , let alone moved to preserve it. Therefore, in this era get involved use of mobile devices such as smartphones as the most efficient tool as interactive learning media. Now, the use of smart mobile devices are no longer limited by age, therefore developers will try to exploit this as a media that can be used for interactive learning.Puppets as one of traditional Indonesian art is very typical of Indonesia. Aside from the form or shape, it can be seen also particularities of the story and the character of each puppet characters . Games that are culturally especially puppet is still rare, especially for mobile devices based on its iOS operating system. Thus the authors tried to make a game design that aims to increase knowledge about the names of the puppet characters.Game development tool use to make this game is GameSalad, with object -oriented programming concepts. GameSalad is one of game development tools that game developers can use to facilitate the making of the game for mobile devices based on the iOS operating system. The design phase begins with analysis requirement and system design. Implementation stage is done by building and developing the game in accordance with the draft that has been made, the implementation of the program. The testing phase is done with a black-box method.The results show that this game can run well on mobile devices with the iOS operating system. The buttons and functions on the game also can function properly and in accordance with their respective functionality. Based on the assessment provided by a sample of users, the game "Gelembung Huruf (Tokoh Wayang)” is considered attractive, easy to understand and play, able to gain knowledge about the names of the puppet characters, raises curiosity, as well as look good game, so the user's attention to play this game again.